Pelatihan Pembukuan Sederhana pada Pelaku UMKM di Sedayu Bantul Yogyakarta - Legina Steisi Pandensolang; Ika Wulandari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This community service activity aims to increase the understanding and skills of MSME players in carrying out simple, effective financial records. This training focuses on recording cash, calculating profits and losses, and separating personal and business finances. This program is aimed at MSMEs Pop Chicken and Rudi meatballs in Argumulyo Village, Sedayu District, Bantul Regency, Yogyakarta, and will be implemented from 26 August to 14 September 2024. The methods used in this activity are surveys, training and counseling, and evaluation. they are carried out through a post-test to measure the understanding of MSME players before and after training in understanding the importance of simple bookkeeping. The results of this activity show that MSME players better understand the importance of neat and structured bookkeeping and are aware of the financial risks that may occur if recording is not done properly.